Study on PAH degrading bacteria isolated from dioxin contaminated soil in Vietnam - Minh, Nguyen Hong; Hanh, Nguyen Thi; Hop, Duong Van; Hang, Dinh Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 26 No 1, 2010)
Abstract